Religion and politics in America : the rise of Christian Evangelists and their impact - Zakaullah, Muhammad Arif (Al-Zaytouna Centre for Studies and Consultations, 2007)
The author starts with a look on the current situation between America and the Muslim World, that "has been exploited by extremists in both camps endangering world peace in the first decade of the 21st century." Then he justifies the major reasons behind his research: "The peace loving majorities in both the west and the Muslim world want to know the causes of this problem to resolve it. The hawks in the west have developed a number of approaches (e.g. Islamophobia, clash of civilizations, etc.) to explain this situation to their people and the world at large. These approaches put the entire blame on Muslims and Islam. On the other hand in the Muslim world it is the other way around as all the explanatory models put the entire blame on the west and Israel.